DETERMINAN CSR DENGAN MODERASI KINERJA KEUANGAN PADA PERUSAHAAN NON KEUANGAN DI INDONESIA - Audric Emerson; Elsa Imelda (Jurnal Paradigma Akuntansi, 2026)
This study aims to determine the effect of managerial ownership and institutional ownership on corporate social responsibility, as well as the moderating effect of financial performance in non-financial companies listed on the Indonesia Stock Exchange during the 2019-2021 period. The sample used amounted to 432 data with the purposive sampling technique. Data processing techniques uses EViews 12. The results of this study indicate that managerial ownership and institutional ownership have a significant negative effect on corporate social responsibility. Then the results of the moderation effect test show that financial performance moderates and weakens the relationship between managerial ownership and corporate social responsibility, and does not moderate the relationship between institutional ownership and corporate social responsibility.